Elevated Serum Levels of CCL23 Are Associated with Poor Outcome after Resection of Biliary Tract Cancer - Christoph Roderburg; Simon Labuhn; Jan Bednarsch; Sven A. Lang; Anne T. Schneider; Linda Hammerich; Mihael Vucur; Tom F. Ulmer; Ulf P. Neumann; Tom Luedde; Sven H. Loosen (Hindawi Limited, 2022)
Background. Surgical tumor resection is the only potentially curative treatment option for patients with biliary tract cancer (BTC). However, 5-year survival rates are still below 50% mainly due to tumor recurrence. The preoperative identification of ideal surgical candidates has remained a major challenge and easily accessible algorithms including parameters of the individual tumor biology are missing. Chemokine (C-C motif) ligand 23 (CCl23) has been associated with tumor progression in hepatocellular carcinoma (HCC), but its role in the context of BTC is largely unknown. Here, we evaluated circulating levels of CCL23 as potential diagnostic and prognostic biomarker in patients with resectable BTC. Methods. CCl23 serum levels were analyzed by multiplex immunoassay in a cohort of 119 BTC patients receiving surgical tumor resection as well as 50 healthy control samples and 11 patients with primary sclerosing cholangitis (PSC). Results. Baseline serum CCL23 levels were significantly elevated in BTC patients compared to PSC patients as well as healthy controls. CCL23 increased the diagnostic sensitivity and specificity of established tumor markers including CA19-9 and correlated with patients' age and makers of systemic inflammation. Elevated preoperative CCL23 levels were associated with a significantly impaired postoperative outcome. BTC patients with a preoperative CCL23 level above the optimal prognostic cut-off value of 702.4 pg/ml showed a median OS of only 110 days compared to 501 days for patients with low initial CCL23 levels. The prognostic value of circulating CCL23 was confirmed in Cox-regression analysis. Conclusion. Serum levels of CCL23 are elevated in patients with BTC, and high preoperative CCL23 levels were associated with an impaired postoperative survival. CCL23 serum levels could help to identify the ideal surgical candidates for BTC resection in the future.